Pengaruh Islam Terhadap Kalender Masyarakat Jawa - Masruhan Masruhan (Al-Mizan (e-Journal), 2017)
The entry of Islam in Java resulted in a meeting of new cultures into the level of community life in Java. This study aims to provide an overview of the cultural influences brought by Islam to previous cultures that already exist in Java, especially in the community calendar system used. The results of the study show that Javanese society before the arrival of Islam has several calendar of Pranatamangsa calendar (calendar season) and calendar Saka or Java (calendar from Hindu India). After the entry of Islam, bring a new calendar of the Hijri calendar. Then In the year 1625 M, Sri Sultan Muhammad or famous with Sultan Agung Anyokrokusumo trying hard to spread the religion of Islam on the island of Java in the kingdom of Mataram by issuing a decree to change the calendar Saka. The calendar dates in Java were used until the 17th century, since that time the acculturation of two calendars, the Hijri calendar with the calendar Saka, the result of change is by changing the months on the calendar Saka into the calendar month of Hijri and Calendar Saka calendar is replaced by the term hijaiyah in the Qur'an.